Lithium-rich positive electrode material and preparation method and application thereof

By forming a composite structure with a layered graphite structure through mixing and calcination, the method addresses the challenge of attaching lithium-rich ternary materials to current collectors, enhancing energy density and safety in lithium-ion batteries.

CN119153661AActive Publication Date: 2024-12-17NANCHANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411414158.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-17
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Existing lithium-rich ternary materials are difficult to attach to current collectors in large quantities, limiting the unit area loading and affecting the energy density, charge and discharge efficiency, and safety of lithium-ion batteries.

Method used

A method involving mixing nano lithium-rich ternary material with a saccharide substance, followed by calcination in an oxygen-rich atmosphere, forms a composite structure with a layered graphite structure, enhancing adhesion to the current collector and improving uniformity and loading capacity.

Benefits of technology

The method enhances the adhesion and uniform distribution of the lithium-rich positive electrode material on the current collector, improving energy density, charge and discharge efficiency, and safety of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153661A_ABST
    Figure CN119153661A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-rich positive electrode material as well as a preparation method and application thereof, and relates to the technical field of lithium battery positive electrode materials. The preparation method provided by the invention comprises the following steps: mixing and grinding a nano lithium-rich ternary material and a carbohydrate according to a mass ratio of 1: (0.5-4), calcining at 450-600 DEG C in an atmosphere with the oxygen content of 20-100%, and cooling to obtain the lithium-rich positive electrode material, the nanometer lithium-rich ternary material is Li < 1.2 > Ni < 0.13 > Co < 0.13 > Mn < 0.54 > O < 2 > with a layered crystal structure. According to the preparation method, the carbohydrate and the nano lithium-rich ternary material are mixed and calcined, so that the carbohydrate forms a layered graphite structure with more defects and is well compounded with the nano lithium-rich ternary material to form a micron-sized structural unit, and the adhesiveness of the lithium-rich positive electrode material on a current collector is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery positive electrode materials, and in particular to a lithium-rich positive electrode material and a preparation method and application thereof. Background Art

[0002] The impact of unit area loading on positive electrode materials is mainly reflected in the energy density and charge and discharge performance of the battery. Unit area loading refers to the content of active substances per unit area of ​​positive electrode materials, which directly affects the energy output and charge and discharge efficiency of the battery. On the premise of ensuring battery safety and stability, increasing the unit area loading can increase the energy density of the battery, improve the charge and discharge efficiency, and thus improve the performance of the battery. However, too small a unit area loading may cause the current density of the battery to be too large during the charge and discharge process, increase the internal resistance of the battery and the risk of thermal runaway, thereby affecting the safety and stability of the battery. Therefore, when selecting positive electrode materials, it is necessary to set a suitable unit area loading by comprehensively considering factors such as energy density, safety, cycle life and cost while ensuring battery performance.

[0003] Lithium-rich ternary materials are a very promising positive electrode material for lithium-ion batteries. Currently, most of the lithium-rich ternary materials prepared are nanometer-scale. Under the existing electrode process conditions, such materials cannot be attached to the current collector in large quantities. Increasing the loading capacity per unit area is a factor that must be considered in the process of commercialization. Summary of the invention

[0004] The purpose of the present invention is to provide a lithium-rich positive electrode material and a preparation method and application thereof.

[0005] In a first aspect, the present invention provides a method for preparing a lithium-rich positive electrode material, comprising: mixing and grinding a nano lithium-rich ternary material and a saccharide substance in a mass ratio of 1: (0.5-4), calcining at 450-600°C in an atmosphere with an oxygen content of 20-100%, and cooling to obtain a lithium-rich positive electrode material; the nano lithium-rich ternary material is a Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0006] The preparation method provided by the present invention is beneficial to improving the uniformity of the two by mixing the sugar substance with the nano lithium-rich ternary material. In addition, heating and calcining at 450-600°C can carbonize the sugar substance, thereby forming a layered graphite structure with more defects and well compounding with the nano lithium-rich ternary material to form a micron-sized structural unit, thereby improving the adhesion of the lithium-rich positive electrode material on the current collector.

[0007] Optionally, the particle size of the nano lithium-rich ternary material is 50-200nm.

[0008] Optionally, the sugar substance includes one of glucose and sucrose.

[0009] Optionally, the nano lithium-rich ternary material and the sugar substance are ball-milled and mixed at a rotation speed of 20-600 rpm.

[0010] Optionally, the calcination process at 450-600° C. in an atmosphere with an oxygen content of 20-100% includes: heating the mixed and ground solids to 450-600° C. at a rate of 5-50° C. / min in an atmosphere with an oxygen content of 20-100%.

[0011] Optionally, the atmosphere with an oxygen content of 20-100% includes an air atmosphere.

[0012] In a second aspect, the present invention provides a lithium-rich positive electrode material prepared by any of the above optional preparation methods, wherein the particle size of the lithium-rich positive electrode material is 50-200 nm.

[0013] In a third aspect, the present invention further provides a lithium-ion battery, comprising a current collector, on which is loaded a lithium-rich positive electrode material prepared by any of the optional preparation methods described above or the lithium-rich positive electrode material.

[0014] Optionally, the loading amount of the lithium-rich cathode material on the current collector is 20-100 mg / cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A physical picture of an electrode sheet obtained by attaching the lithium-rich positive electrode material provided in Example 1 of the present invention to a current collector;

[0016] Figure 2 A physical picture of an electrode sheet obtained by attaching a lithium-rich positive electrode material provided in Example 2 of the present invention to a current collector;

[0017] Figure 3 A physical picture of an electrode sheet obtained by attaching the lithium-rich positive electrode material provided in Comparative Example 4 of the present invention to a current collector;

[0018] Figure 4 A charge and discharge performance curve of a button battery made of the lithium-rich positive electrode material provided in Example 1 of the present invention;

[0019] Figure 5 This is a charge and discharge performance curve of a button battery made of the lithium-rich positive electrode material provided in Example 2 of the present invention. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0021] The invention provides a method for preparing a lithium-rich positive electrode material, comprising: mixing and grinding a nano lithium-rich ternary material and a sugar substance in a mass ratio of 1:(0.5-4), calcining at 450-600°C in an atmosphere with an oxygen content of 20-100%, and cooling to obtain the lithium-rich positive electrode material.

[0022] In fact, the present invention helps to improve the uniformity of the particle sizes of the nano-lithium-rich ternary material and the sugar substance by mixing and grinding the nano-lithium-rich ternary material and the sugar substance, and can also promote the uniform distribution of the two, thereby facilitating the formation of a composite structure in the subsequent calcination process.

[0023] In fact, the present invention can effectively adjust the content of lithium in the lithium-rich positive electrode material after calcination by mixing the nano-lithium-rich ternary material with the sugar substance in a mass ratio of 1: (0.5-4), and can also effectively ensure the uniform distribution of the nano-lithium-rich ternary material on the layered graphite structure formed after the carbonization of the sugar substance.

[0024] Specifically, when the nano lithium-rich ternary material is mixed with the sugar substance, the nano lithium-rich ternary material used is Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, in fact, by using this nano lithium-rich ternary material, the lithium content in the positive electrode material can be effectively increased. At the same time, its layered crystal structure can be well composited and interwoven with the layered graphite structure after carbonization of sugar substances, thus forming a stable structural unit.

[0025] In some embodiments, the particle size of the nano lithium-rich ternary material is 50-200nm. By selecting lithium-rich materials in this particle size range, they can be effectively combined in the layered graphite structure formed after the carbonization of sugar substances, and help the distribution of the formed lithium-rich positive electrode material on the current collector.

[0026] In some embodiments, when the nano lithium-rich ternary material is mixed with a sugar substance, the sugar substance used includes one of glucose and sucrose. In fact, by selecting economical and common glucose or sucrose, the manufacturing cost of lithium-rich positive electrode materials can be effectively reduced, which is conducive to large-scale industrial production. At the same time, after carbonization, glucose and sucrose have good conductivity, which helps to improve the performance and charge and discharge efficiency of the positive electrode material.

[0027] In fact, when the nano-lithium-rich ternary material is mixed and ground with the sugar substance, ball milling is performed at a rotation speed of 20-600rpm, which is beneficial to improve the mixing uniformity and particle size uniformity of the nano-lithium-rich ternary material and the sugar substance. At the same time, after ball milling, the surface defects of the nano-lithium-rich ternary material can be increased, thereby improving the surface activity of the nano-lithium-rich ternary material, which is beneficial to compounding in the subsequent calcination process.

[0028] In some embodiments, when the nano lithium-rich ternary material and the sugar substance are ball-milled, zirconium oxide is used as the ball milling ball, and the ball-to-material ratio is controlled to be (10-20):1, which is conducive to fully mixing the nano lithium-rich ternary material and the sugar substance. In fact, the rotation speed during the ball milling process is preferably 50-300rpm, and more preferably 100-200rpm.

[0029] In some embodiments, the process of calcining at 450-600°C in an atmosphere with an oxygen content of 20-100% includes: heating the mixed and ground solids to 450-600°C at a rate of 5-50°C / min in an atmosphere with an oxygen content of 20-100%. In fact, by continuously heating with the atmosphere temperature, it is helpful to improve the uniformity of the temperature rise of the solids and avoid the deterioration of the nano-lithium-rich ternary materials and sugar substances in the solids when the temperature changes drastically. In fact, by calcining the solids at 450-600°C, it is beneficial to carbonize the sugar substances and avoid reducing the oxygen in the nano-lithium-rich ternary materials.

[0030] In some embodiments, the atmosphere having an oxygen content of 20-100% includes an air atmosphere.

[0031] In fact, the present invention also provides a lithium-rich positive electrode material prepared by any of the above preparation methods, and the particle size of the lithium-rich positive electrode material is 50-200 nm.

[0032] At the same time, the present invention also provides a lithium-ion battery, comprising a current collector, and the current collector is loaded with a lithium-rich positive electrode material prepared by any of the above preparation methods. In fact, the loading amount of the lithium-rich positive electrode material on the current collector is 20-100 mg / cm 2 , preferably 20-25 mg / cm 2 .

[0033] In fact, when preparing a current collector loaded with a lithium-rich cathode material, the following steps are included:

[0034] S1. Mixing and dissolving a lithium-rich positive electrode material, conductive carbon black and polyvinylidene fluoride in a solvent at a mass ratio of 8:1:1 to prepare an electrode slurry;

[0035] S2. Apply the electrode slurry on a current collector and dry it to obtain a current collector loaded with a lithium-rich positive electrode material.

[0036] Specifically, the solvent used in step S1 is N-methylpyrrolidone. In fact, the solvent in step S1 can be selected from electrode solvents commonly used in the art, and the amount used is necessary to completely dissolve the lithium-rich positive electrode material, conductive carbon black and polyvinylidene fluoride.

[0037] Similarly, when the electrode slurry is coated on the current collector in step S2, the coating method used can be common coating methods such as rolling, dipping, brushing, etc., so that the electrode slurry can be evenly distributed on the current collector.

[0038] Example 1

[0039] This embodiment 1 provides a method for preparing a lithium-rich positive electrode material, comprising the following steps: 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and glucose were mixed in a mass ratio of 1:0.5, and then ball-milled at 100 rpm in a ball mill using zirconium oxide as ball milling balls to obtain a mixture; the mixture was heated to 500°C at a rate of 10°C / min in an air atmosphere and then cooled to room temperature to obtain a lithium-rich positive electrode material with an average particle size of 100 nm.

[0040] Example 2

[0041] This embodiment 2 provides a method for preparing a lithium-rich positive electrode material, comprising the following steps: 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and glucose were mixed in a mass ratio of 1:4, and then ball-milled at 100 rpm in a ball mill using zirconium oxide as ball milling balls to obtain a mixture; the mixture was heated to 500°C at a rate of 10°C / min in an air atmosphere and then cooled to room temperature to obtain a lithium-rich positive electrode material with an average particle size of 100 nm.

[0042] Comparative Example 1

[0043] This comparative example 1 provides a method for preparing a lithium-rich positive electrode material, comprising the following steps: 1.2 Ni 0.13 Co0.13 Mn 0.54 O2 and glucose were mixed in a mass ratio of 1:0.5, and then ball-milled at 100 rpm in a ball mill using zirconium oxide as ball milling balls to obtain a mixture; the mixture was heated to 400°C at a rate of 10°C / min in an air atmosphere and then cooled to room temperature to obtain a lithium-rich positive electrode material with an average particle size of 100 nm.

[0044] Comparative Example 2

[0045] This comparative example 2 provides a method for preparing a lithium-rich positive electrode material, comprising the following steps: 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and glucose were mixed in a mass ratio of 1:0.5, and then ball-milled at 100 rpm in a ball mill using zirconium oxide as ball milling balls to obtain a mixture; the mixture was heated to 400°C at a rate of 10°C / min in an argon atmosphere and then cooled to room temperature to obtain a lithium-rich positive electrode material with an average particle size of 100 nm.

[0046] Comparative Example 3

[0047] This comparative example 3 provides a method for preparing a lithium-rich positive electrode material, comprising the following steps: 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and glucose were mixed in a mass ratio of 1:0.5, and then ball-milled at 100 rpm in a ball mill using zirconium oxide as ball milling balls to obtain a mixture; the mixture was heated to 500°C at a rate of 10°C / min in an argon atmosphere and then cooled to room temperature to obtain a lithium-rich positive electrode material with an average particle size of 100 nm.

[0048] Comparative Example 4

[0049] This comparative example 4 provides a method for preparing a lithium-rich positive electrode material, comprising the following steps: 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and glucose were mixed in a mass ratio of 1:1, and then ball-milled at 100 rpm in a ball mill using zirconium oxide as ball milling balls to obtain a mixture; the mixture was heated to 500°C at a rate of 10°C / min in an argon atmosphere and then cooled to room temperature to obtain a lithium-rich positive electrode material with an average particle size of 100 nm.

[0050] Performance Testing

[0051] The lithium-rich positive electrode materials prepared in Examples 1 to 2 and Comparative Examples 1 to 4 are loaded on copper foil to prepare electrode sheets, comprising the following steps:

[0052] S1. Mix and dissolve the lithium-rich positive electrode material, conductive carbon black and polyvinylidene fluoride in N-methylpyrrolidone in a mass ratio of 8:1:1 to prepare an electrode slurry;

[0053] S2, the electrode slurry was coated on the copper foil and dried to obtain a loading of 20 mg / cm 2 of electrode sheets.

[0054] Among them, the surface of the electrode sheet made of the lithium-rich positive electrode material prepared in Comparative Example 4 cracked and fell off. Figure 3 As shown, the surface of the electrode sheet made of the lithium-rich positive electrode material prepared in Examples 1 to 2 and Comparative Examples 1 to 3 is smooth and crack-free. The actual image of the electrode sheet made of the lithium-rich positive electrode material in Example 1 is as shown Figure 1 As shown, the actual image of the electrode sheet made of the lithium-rich positive electrode material in Example 2 is as follows Figure 2 shown.

[0055] The lithium-rich positive electrode materials prepared in Examples 1 to 2 and Comparative Examples 1 to 3 were made into electrode sheets, and then packaged with lithium sheets into button cells. Then, charge and discharge tests were performed at a current density of 15 mA / g. The charge and discharge performances of the button cells corresponding to Examples 1 to 2 were as follows: Figure 4 and Figure 5 , while the button batteries corresponding to Comparative Examples 1 to 3 have no electrical performance.

[0056] from Figure 4 and Figure 5 It can be seen that the specific capacities of the button batteries corresponding to Examples 1 and 2 are 200 mA / g and 190 mA / g, respectively.

[0057] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for preparing a lithium-rich positive electrode material, characterized in that: include: The nano lithium-rich ternary material and the sugar substance are mixed and ground in a mass ratio of 1: (0.5-4), calcined at 450-600°C in an atmosphere with an oxygen content of 20-100%, and then cooled to obtain a lithium-rich positive electrode material; the nano lithium-rich ternary material is a layered crystal structure of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

2. The preparation method according to claim 1, characterized in that: The particle size of the nano lithium-rich ternary material is 50-200nm.

3. The preparation method according to claim 1, characterized in that: The sugar substance includes one of glucose and sucrose.

4. The preparation method according to claim 1, characterized in that: The nano lithium-rich ternary material and the sugar substance are ball-milled and mixed at a rotation speed of 20-600 rpm.

5. The preparation method according to claim 1, characterized in that: The process of calcining at 450-600° C. in an atmosphere with an oxygen content of 20-100% comprises: heating the mixed and ground solids to 450-600° C. at a rate of 5-50° C. / min in an atmosphere with an oxygen content of 20-100%.

6. The preparation method according to claim 1, characterized in that: The atmosphere having an oxygen content of 20-100% includes an air atmosphere.

7. A lithium-rich positive electrode material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The particle size of the lithium-rich positive electrode material is 50-200 nm.

8. A lithium ion battery, characterized in that: It comprises a current collector, on which is loaded a lithium-rich positive electrode material prepared by the preparation method according to any one of claims 1 to 6 or a lithium-rich positive electrode material according to claim 7.

9. The lithium-ion battery according to claim 8, characterized in that: The loading amount of the lithium-rich positive electrode material on the current collector is 20-100 mg / cm 2 .

Citation Information

Patent Citations

  • Method for modifying surface of anode material Li1.2Ni0.13Co0.13Mn0.54O2 for lithium ion battery

    CN104659354A

  • Solid-phase reaction synthesis method of electrode active material single crystal

    CN111485278A

  • Lithium-rich ternary positive electrode material and preparation method and application thereof

    CN115140784A

  • Composite lithium-rich material and preparation method thereof, positive pole piece and secondary battery

    CN117878450A